The Bracelet - Love, Dorothy 1949- (Thorndike, Maine : Center Point Large Print, 2015)
"The story of a young southern woman whose dreams fracture under the weight of her family's tragic past"--
Keywords: Family secrets -- Fiction; Large type books; Savannah (Ga.) -- Fiction -- History -- 19th century; Historical fiction